BETWEEN THE DEVIL AND THE DEEP BLUE SEA: NIGER DELTA WOMEN AND THE BURDEN OF GAS FLARING - Omeire, Edward Uche; Aveuya, Agbatse Augustine; Muoneme – Obi, Chinedu. T; Gold, Adolphus; Akudo, Ufomba; Omeire, Chinemerem Adaiheoma (European Scientific Journal, ESJ, 2014)
This paper examines the impact of gas flaring on Niger Delta Women. The findings of the study show that gas flaring impact men and women disappropriately, with women being more exposed and vulnerable due to a number of associated cultural and socio-economic factors. It was also observed that gas flaring ritual has continued endlessly in Niger Delta due to a number of factors which include: lack of political will, lack of sound and broad regulatory framework, high level of corruption and lack of patriotism among state actors and above all, insincerity and lack of environmental accountability among multi-national oil companies operating in the Niger delta. The authors therefore conclude that there is the urgent need to mainstream gender in oil and gas policies in Nigeria. There is also the need to put in place a sound and broad regulatory framework that will compel multi-national oil companies operating in the Niger delta to be environmentally accountable to the people.